Socio-economic return analysis of apple farming in Mustang district of Nepal - Khatri, Bishnu Bahadur; Pasa, Rajan Binayek; Purja, Chandra; Adhikari, Devendra (Journal of Agriculture and Natural Resources, 2024)
Apple farming is commercially done in mountainous regions in Nepal. The aim of this study was to assess social and economic returns of apple farming in Mustang district. The study applied a quantitative approach using multi-site case study methodology. The primary data were collected from 156 respondents by using reliable (Cronbach’s alpha 0.70) self-administered questionnaires. The study revealed that the mean age, household size, and ethnicity were 49 years, 6 members, and 80% Janajati, respectively. The mean value of irrigated land, non-irrigated land, and leasehold land was found to be 0.59 ha, 0.11 ha, and 0.18 ha respectively. The majority of households (48.7%) have food sufficiency for 6-9 months. Apple farming has enhanced farmers’ living standards and quality of life, with improved access to nutritious food and perceived family well-being while creating 464 self-employment and 758 seasonal jobs. The economic analysis showed that the average initial investment in farm businesses as well as income from agriculture and agro-based entrepreneurship were found US 1,864, US 5,523 and US 6,720 respectively. Likewise, average annual expenses for new seeds, fertilizers/pesticides/vitamins, labor, irrigation, and technician visit fee found US 354; 1,089; 1,551; 59, and 64 respectively. The annual income from apple farming is 75% associated with annual expenses for technician’s fee, fertilizers/pesticide/vitamin, new seeds, irrigation, and labor. Besides, the variables of expense for fertilizer/pesticide/vitamin (t= 2.99, p<0.05), irrigation (t= 0.36, p<0.05), and labor (t= 5.32, p <0.05) are significantly associated with annual income. Respondents with irrigation facilities had higher annual incomes than those without. Apple farming in Mustang is a key income source, offering significant social and economic benefits. However, issues like inadequate cold storage, poor roads, and retailer monopolies persist. These findings provide valuable insights for policymakers, planners, and technicians advancing apple farming commercialization in Nepal.